A study of electricity market models in the restructured electricity supply industry - Hassan, Mohammad Yusri; Hussin, Faridah; Othman, Mohd. Fauzi (Faculty of Electrical Engineering, 2009)
In the new era of modernity, the competitive environment has spread widely into all sectors including the electricity market which began since 1980s. A number of market models have been introduced and each model was designed appropriately with its local condition. The selection of the model used depends on the justification determined by power utilities or regulatory policies taking into account the technical and economic aspect point of view. Looking forward to an opened and competitive electricity trading market, Malaysian Electricity Supply Industry (MESI) has aimed to restructure its current model to become a wholesale market model by taking the first step in 1992 through the introduction of the Independent Power Producers (IPPs). Since then MESI applies the Single Buyer Model which produces no transparent competition either on generation or demand side. Tenaga Nasional Berhad (TNB) is the only company that acts as the power off taker by all power producers and sells the energy to all relevant parties. The purpose of this research is to study in depth the restructuring of electricity supply industry and identifying the advantages and disadvantages for each electricity market models, i.e. existing single buyer, pool and bilateral market model. The economic benefits from the view point of power producers under these models were also analyzed. The findings can be used by the Energy Commission (EC) as a starting point in planning towards the next step of competitive environment. Besides, the current power authority (TNB) and other private investors may also use these findings for their own forecast on the system planning. A case study was carried out in order to compare the three market models in term of generation revenue by using the Matlab Simulation under the real load profiles for peninsular of Malaysia. The results showed that the single buyer is uncompetitive but is controllable as TNB monopolise the market. However, both pool and bilateral market models are able to provide a competitive environment but creates higher risk as the energy price might fluctuate from time to time in practical. This shows that MESI should consider several policies if they plan to apply the alternative market models.